Demographics and awareness of diabetic retinopathy among diabetic patients attending the vitreo-retinal service at a tertiary eye care center in Nepal - Thapa, R; Paudyal, G; Maharjan, N; Bernstein, PS (Nepalese Journal of Ophthalmology, 2012)
Introduction: Diabetic retinopathy (DR) is one of the leading causes of blindness in Nepal. Objective: To investigate the demographic characteristics and awareness of diabetic retinopathy among new cases of diabetes mellitus (DM) attending the vitreo-retinal service of a tertiary eye care centre in Nepal. Materials and methods: A hospital-based, cross-sectional study including all consecutive new cases of DM was carried out. Detailed demographics of the subjects and their awareness of potential ocular problems from diabetes mellitus were noted. Results: A total of 210 patients with a mean age of 57 ± 10.4 years were included. Brahmins (34.8 %) and Newars (34.3 %) were the predominant ethnic groups. Housewives (38.6 %) and office workers (18.6 %) were the major groups affected. Two-fifths (37 %) of the cases were unaware of DR and its potential for blindness. Awareness was significantly higher among literate patients (P = 0.006). Fundus evaluation was done for the first time in 48.6 %, although almost four-fifths had a duration of diabetes of five years or more. DR was found in 78 % of the cases, with 16.7 % already at the proliferative stage and about 40 % exhibiting clinically significant diabetic macular edema. Conclusion: A lack of awareness of DR coupled with a high proportion of cases already at a sight-threatening stage of retinopathy at their first presentation reflects the need for improved awareness programs to reduce the burden of blindness from DR in Nepal. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5844 NEPJOPH 2012; 4(1): 10-16